Peralihan Kekuasaan Presiden dalam Lintasan Sejarah Ketatanegaraan Indonesia - Naimah, Hayatun (UIN Antasari, 2015)
The process of the power transition from President Soekarno to President Soeharto left the story of political issues. One of the important issues marked the downfall of SukarnoaspresidentisNawaksaraincident.ThetransitionfromPresidentSuhartoto President BJ Habibie started with students strikes that forced Suharto to step down from his position as President. The strike was ended with resignation of Soeharto. Therefore, the vice president, Habibie, was appointed to be President. This raised a polemic about the legiticay of Habibie as President. The next power transition is from President Habibie to Abdurrahman Wahid and from President Abdurrahman Wahid to Megawati Sukarnoputri. The transition from President Abdurrahman Wahid to Megawati Sukarnoputri started with the emergence of many participant political parties in the election. It made more than one candidate for President so the election of President was done by MPR. That period is considered as the most democratic power transition process in the history of the Indonesian state administration. Susilo Bambang Yudoyono, who was the president after megawati, was the first president elected by people through direct election.Kata kunci : Peralihan Kekuasaan, Presiden